NAD+ Biosynthesis Impairment and Acute Kidney Injury after Major Vascular Surgery - Annmarie I. Mede; Ginger L. Milne; Dawei Wei; Derek K. Smith; Loren E. Smith (MDPI AG, 2023)
Acute kidney injury (AKI) is a serious complication after vascular surgery. Reduced synthesis of nicotinamide adenine dinucleotide (NAD+) from tryptophan is associated with an increased risk of AKI in critically ill patients, patients hospitalized with COVID-19, and cardiac surgery patients, and is marked by elevated urinary quinolinate and quinolinate to tryptophan ratios. We measured quinolinate concentrations in vascular surgery patients to determine if impaired NAD+ synthesis was associated with AKI in this patient population. Eight preoperative and eight postoperative vascular surgery patients who developed AKI were selected from a parent study to participate in this single-center case-control study. They were matched with controls who did not develop AKI based on age, sex, BMI, eGFR, hypertension, and diabetes. Urinary quinolinate and tryptophan concentrations were measured at anesthetic induction and on postoperative day one. Two-sided Mann-Whitney U tests were used to compare quinolinate and quinolinate to tryptophan ratios. Multivariate linear regression modeling was used to estimate the relationship between quinolinate and serum creatinine. There was no difference in preoperative or postoperative urine quinolinate concentrations or the preoperative quinolinate to tryptophan ratio between patients that did and did not develop AKI (p = 0.07, 0.50, and 0.32, respectively). However, postoperative quinolinate to tryptophan ratios were higher in AKI patients (p = 0.04). Further, after adjustment for AKI risk factors, higher preoperative quinolinate concentrations and higher postoperative quinolinate to tryptophan ratios were associated with greater postoperative creatinine increases (p = 0.04 and 0.04, respectively). These data suggest that impaired NAD+ synthesis may contribute to AKI development in vascular surgery patients.